1994
DOI: 10.1577/1548-8675(1994)014<0797:ecsrha>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Coho Salmon Rearing Habitat and Smolt Production Losses in a Large River Basin, and Implications for Habitat Restoration

Abstract: To develop a habitat restoration strategy for the 8,270‐km2 Skagit River basin, we estimated changes in smolt production of coho salmon Oncorhynchus kisutch since European settlement began in the basin, based on changes in summer and winter rearing habitat areas. We assessed changes in coho salmon smolt production by habitat type and by cause of habitat alteration. We estimated that the coho salmon smolt production capacity of summer habitats in the Skagit River basin has been reduced from 1.28 million smolts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(182 citation statements)
references
References 9 publications
3
179
0
Order By: Relevance
“…In contrast, 460 potadromous species can make use of habitats above and below the same barriers (assuming that sufficient habitat exists on each side of the barrier to sustain a separate population). The increased sensitivity of diadromous species is exemplified by widespread declines of diadromous species (Pacific Rivers Council 1993;Beechie et al 1994;Moyle 1995;Berkamp et al 2000), for which fragmentation loss of connectivity has been at least in part to blame. Nonetheless, the 465 impacts on potadromous fish (e.g.e.g., Moyle 1995;Muhar 1996;Dunham et al 1997;Fagan et al 2002;Morita and Yamamoto 2002) and aquatic invertebrates (Master 1990) are also widespread.…”
Section: Discussion 430mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, 460 potadromous species can make use of habitats above and below the same barriers (assuming that sufficient habitat exists on each side of the barrier to sustain a separate population). The increased sensitivity of diadromous species is exemplified by widespread declines of diadromous species (Pacific Rivers Council 1993;Beechie et al 1994;Moyle 1995;Berkamp et al 2000), for which fragmentation loss of connectivity has been at least in part to blame. Nonetheless, the 465 impacts on potadromous fish (e.g.e.g., Moyle 1995;Muhar 1996;Dunham et al 1997;Fagan et al 2002;Morita and Yamamoto 2002) and aquatic invertebrates (Master 1990) are also widespread.…”
Section: Discussion 430mentioning
confidence: 99%
“…An advantage of the approach presented here is that it allows the evaluation of impacts on individual projects at thea riverscape scale of the entire river network that includes cumulative impacts of many small developments (e.g.e.g.,, Beechie et al 1994;Pringle 2003). As 535 relationships with structural connectivity and biological communities develop through further research in fluvial landscape ecology, a standardized method such as we propose here will allow comparison of multiple watersheds and will aid in identifying extirpation hotspots or areas in need of enhanced protective measures.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kasahara and Wondzell (2003) found that in a model of a wide alluvial valley, removal of secondary channels reduced hyporheic discharge by 25%. Complex off-channel habitats also are important juvenile rearing habitats and have been associated with increased productivity (Beechie et al 1994). Bedform diversity associated with inchannel LWD also has been associated with salmon spawning habitat .…”
Section: Factors Reducing Spawning Habitat Qualitymentioning
confidence: 99%